Experimental and Numerical Study of CFRP Laminate Strengthened Concrete Beams Under Hygrothermal Environment - Eyad Alsuhaibani; Nur Yazdani; Eyosias Beneberu (Advances in Civil Engineering)
Carbon fiber reinforced polymer (CFRP) laminates are widely used to strengthen and retrofit deteriorated concrete structures, yet their long-term performance and durability under varied environmental conditions remain critical areas of investigation. This study comprehensively examined the behavior of small concrete beams externally bonded with CFRP laminates under three distinct hygrothermal regimes: immersion in water at 23, 45, and 60°C for up to 112 days. The experimental program encompassed direct tension pull-off testing of the CFRP–concrete assembly and four-point bending tests on the beams. Pull-off tests revealed complex failure modes, with bonding epoxy failure (43%) and concrete substrate cohesion failure (39%) being dominant. Notably, pull-off strength exhibited nonmonotonic trends across all environments, suggesting that environmental degradation is not solely time-dependent. Flexural capacity increased by 20%, 49%, and 11% for room temperature (RT), moderate temperature (MT), and high temperature (HT) conditions, respectively, after 112 days, highlighting the synergistic effect of CFRP strengthening and ongoing concrete curing. A calibrated three-dimensional finite element model, developed using Abaqus, accurately replicated the experimental results and facilitated parametric studies on factors influencing CFRP-strengthened beam performance. This included concrete compressive strength, number of CFRP layers, laminate thickness, and FRP type. The study elucidates the complex interplay between environmental exposure, material properties, and structural performance, contributing valuable insights for enhancing durability predictions and design guidelines for CFRP-strengthened concrete structures in diverse climatic conditions.